1228. Incidence of Staphylococcus aureus Infection after Elective Surgeries Among Adults in US Hospitals. (26th November 2018) - Dreyfus, Jill; Begier, Elizabeth; Yu, Holly; Quintana, Alvaro; Gayle, Julie; Olsen, Margaret A
Abstract: Background: Staphylococcus aureus is a leading cause of postsurgical infections. National estimates of these infections after elective surgeries based on microbiology data are limited. This study assessed 180-day postsurgical S. aureus incidence in real-world hospital settings. Methods: Adults (≥18 years) who underwent elective surgery during a hospital-based outpatient or inpatient encounter from July 1, 2010–June 30, 2015 at one of 181 hospitals reporting microbiology results in the Premier Healthcare Database (PHD). Eighty-seven surgical categories were defined using ICD-9-CM and CPT procedure codes according to National Hospital Surveillance Network groupings plus additional categories. Microbiology results and ICD-9-CM diagnosis codes were used to identify invasive (e.g., deep incisional and organ-space SSI, bloodstream) and overall (i.e., invasive, superficial incisional, urinary tract, respiratory) S. aureus infections. Cumulative 180-day S. aureus infection rates were calculated as number of infections divided by number of discharges with elective surgeries. National infection volumes were calculated by multiplying infection rates by national inpatient elective surgery estimates using surgery counts in the entire PHD (665 hospitals) and weights based on hospital characteristics. Results: Following 1, 116, 994 hospital-based outpatient elective surgeries, 180-day S. aureus incidence was 1.19% overall, with 0.38% complicated by invasive S. aureus infections. Among 884, 803 inpatient elective surgeries, overall and invasive 180-day S. aureus infection incidence was 1.35% and 0.53%, respectively. This translated to an estimated 57, 200 S. aureus infections (22, 400 invasive) among an estimated 4.2 million elective inpatient surgeries annually in the US methicillin-resistance (MRSA) was observed in 45% and 46% of S. aureus infections after inpatient and outpatient surgeries, respectively. Figure 1 shows cumulative S. aureus incidence rates at each time point after outpatient and inpatient elective surgeries. Figure 2 delineates the incidence rates for each type of S. aureus infection. Conclusion: Our study indicated similar S. aureus infection rates after inpatient and outpatient elective surgeries. The results highlight the much larger burden of disease of S. aureus infection in the United States beyond inpatient surgeries. Disclosures: J. Dreyfus, Premier, Inc.: Employee and Shareholder, Salary. E. Begier, Pfizer, Inc.: Employee and Shareholder, Salary. H. Yu, Pfizer, Inc.: Employee and Shareholder, Salary. A. Quintana, Pfizer, Inc.: Employee and Shareholder, Salary. J. Gayle, Premier, Inc.: Employee, Salary. M. A. Olsen, Pfizer: Consultant, Consulting fee.